2020
DOI: 10.3390/nu12092809
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Energy Wasting Assessment and Clinical Outcomes in Patients with Acute Kidney Injury: A Systematic Review with Meta-Analysis

Abstract: Nutritional assessment is essential to identify patients with acute kidney injury (AKI) who are protein-energy wasting (PEW) and at risk of poor clinical outcomes. This systematic review aimed to investigate the relationship of nutritional assessments for PEW with clinical outcomes in patients with AKI. A systematic search was performed in PubMed, Scopus, and Cochrane Library databases using search terms related to PEW, nutrition assessment, and AKI to identify prospective cohort studies that involved AKI adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(127 reference statements)
1
12
0
Order By: Relevance
“…A meta-analysis showed that protein-energy wasting (PEW) assessed using subjective global assessment (SGA) was associated with greater mortality risk (RR: 1.99, 95% CI: 1.36–2.91). Individual nutrition parameters, such as serum chemistry, body mass, muscle mass, and dietary intake, were not consistently associated with mortality in patients with AKI [ 30 ]. Our study showed that the mNUTRIC score was an effective tool to evaluate the prognosis of AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that protein-energy wasting (PEW) assessed using subjective global assessment (SGA) was associated with greater mortality risk (RR: 1.99, 95% CI: 1.36–2.91). Individual nutrition parameters, such as serum chemistry, body mass, muscle mass, and dietary intake, were not consistently associated with mortality in patients with AKI [ 30 ]. Our study showed that the mNUTRIC score was an effective tool to evaluate the prognosis of AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-energy wasting (PEW), a state of decreased body protein mass and energy fuel, is frequently observed in chronic kidney disease (CKD) patients [ 1 ]. The PEW, a CKD-specific nutritional disorder, affects various clinical outcomes [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Screening tools such as subjective global assessment (SGA), nutritional risk screening 2002 (NRS 2002), short nutritional assessment questionnaire, malnutritional screening tool, mini nutritional assessment, and malnutritional universal screening tool are widely used in patients with chronic kidney disease (CKD) where the association with worse outcomes is well‐established 12 . However, in AKI, SGA and NRS 2002 are the only validated tools 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…During inflammation, the rate of albumin production is reduced while the rate of degradation is increased 19 . There is inconsistent evidence for the association of albumin and mortality in AKI patients 13 …”
Section: Introductionmentioning
confidence: 99%